Association of Subclinical Hypothyroidism With Anxiety Symptom in Young First-Episode and Drug-Naïve Patients With Major Depressive Disorder - Yang, Ruchang; Du, Xiangdong; Li, Zhe; Zhao, Xueli; Lyu, Xiaoli; Ye, Gang; Lu, Xinchuan; Zhang, Guangya; Li, Chuanwei; Yue, Yan; Wu, Yuxuan; Peng, Ruijie; et al. (Frontiers in Psychiatry, 2022)
Backgrounds Subclinical hypothyroidism (SCH) was reported to be associated with depression; however, its role in coexisting anxiety symptom in young patients with major depressive disorder (MDD) remains unclear. The objective of this study was to explore the relationship between SCH and anxiety symptom in young first-episode and drug-naïve (FEDN) MDD patients. Methods A total of 520 outpatients diagnosed as FEDN MDD with SCH were recruited in this study. Their socio-demographic, clinical data and thyroid function parameters were collected. The Hamilton Anxiety Rating Scale (HAMA) and the Hamilton Depression Rating Scale (HAMD) were employed to measure the severity of anxiety symptom and depressive symptom, respectively. Based on the HAMA scores, patients who scored ≥ 25 were defined as anxious major depressive disorder (A-MDD) while others as non-anxious major depressive disorder (NA-MDD). Results The prevalence rate of A-MDD was 15.8% in young FEDN MDD patients with comorbid SCH. Moreover, serum thyroid stimulating hormone (TSH) levels were significantly higher in patients with A-MDD compared with those with NA-MDD (p < 0.001). Multivariate binary logistic regression analysis indicated that A-MDD was associated with serum TSH levels with an odds ratio (OR) of 1.602. Serum TSH level of 6.17 mIU/L was the critical value to distinguish A-MDD and NA-MDD, with sensitivity of 0.805 and specificity of 0.539. There were no statistically significant differences between NA-MDD and A-MDD patients in terms of socio-demographic variables, serum free triiodothyronine (FT3), free thyroxine (FT4), thyroid peroxidases antibody (TPOAb) and anti-thyroglobulin (TgAb) levels. Conclusions A-MDD patients presented higher serum TSH level. It is suggested that serum TSH level may be a potential biomarker for predicting moderate and severe anxiety symptoms in young FEDN MDD patients with SCH.